Don't touch my smartphone! The psychological and sensory-motivational factors of problematic smartphone and social media use in emerging adulthood - Giancola, Marco; Perazzini, Matteo; Bontempo, Danilo; Perilli, Enrico; D'Amico, Simonetta (Frontiers in Developmental Psychology, 2025)
This study examined whether need for touch predicts problematic smartphone use (PSU) and problematic social media use (PSMU), beyond psychological factors, including narcissism (grandiose and vulnerable), fear of missing out (FoMO), and emotion regulation strategies (cognitive reappraisal and emotion suppression). A total of 430 emerging adults (Mage = 19.50, SD = 1.12; 50% female) completed an online survey. Hierarchical regression analyses revealed that need for touch significantly predicted both PSU and PSMU, with a stronger effect on PSU, suggesting that haptic gratifications may drive smartphone engagement beyond social media use. These findings extend previous research by demonstrating that need for touch is a robust contributor to problematic digital behaviors. In addition, they underscore the need to integrate sensory-motivational drivers into theoretical models of PSU and PSMU and highlight the relevance of sensory-based approaches in future clinical intervention strategies. Limitations and future research directions are discussed.